An Analysis of Madrasah Aliyah Students’ Ability in Writing Recount Text - Hasanah, Iradatul (MAN 4 Kota Pekanbaru, 2022)
Students' ability in writing varies greatly; some students can write recount text, but on the other hand, others don't have that capability. This study focus on five aspects of writing. They are Grammar, Vocabulary, Mechanic, Organization, and Fluency. This study aims to find out the ability of Tenth Grade Students of MAN 4 Kota Pekanbaru in writing recount text. The data collecting technique is using a writing test. The research findings are as follows: first, the Tenth Grade student of MAN 4 Kota Pekanbaru's ability to write recount text is at a good level with an average score of 64.75. Second, the student's average score in terms of Grammar is 61.80, Vocabulary is 69, Mechanic is 70.02, Organization is 61.80, and Fluency is 52.40. This component is the most challenging problem the students face in writing recount texts. This result concluded that the tenth-grade students of MAN 4 Pekanbaru have a relatively good level of writing recount texts. But with an average score of 62.75, they need to practice more in writing a text.